Between rurality and urbanity: Indicators of social integration of Albanian rural to urban migrants - Titili , Denisa; Nikaj , Irena (European Journal of Multidisciplinary Studies, 2023)
Integration of rural to urban migrants represents a complex experience of learning and adapting to a community with a new and different culture. Despite the changes in the way of living and the modifications of cultural values due to social interaction and coexistence with urban subculture, most of migrants moved from village to the city retain a sense of rurality. Internal migration in Albania often takes place in form of chain migration. Therefore, the concentration of migrants to the peripheral part of the city, rural social networks, kinship interaction, financial and social support impact their social and cultural integration to urban subculture. This paper aims to highlight indicators of social integration of Albanian migrants moved from village to the city. Data for this paper was obtained through a quantitative survey method. 400 surveys were conducted with Albanian migrants moved from villages to Korça city which remains the second most important destination, besides Tirana, for migrants from rural areas of the southeastern part of Albania. Descriptive and correlative statistical analysis was used for data interpretation. Rurality is not only a territorial unit, but derives from socially created meanings. The study showed that sense of rurality impacts the patterns and strategies of integration of rural to urban migrants to the city.